Implementasi Pembelajaran Tahfidz Al-Qur’an Dalam Membentuk Karakter Islami di SMAN 1 Batusangkar - Refnaldi (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
This research aims to determine the steps for character education through the Tahfidz Al Qur'an program at SD I Batusangkar, to identify the Islamic character of students at SMAN I Batusangkar through the Tahfidz Al Qur'an program. This research uses a qualitative descriptive research type with data triagulation analysis techniques. To obtain information, researchers used interview techniques, observation and documentation with the subject teachers and school principals. Based on the results obtained: Steps for Islamic character education through learning Tahfidz Al Qur'an at SNAN I ; SMAN I Batusangkar has provided a form and pattern of Islamic character education in learning Tahfidz Al Qur'an which includes 5 characters, namely: Religious, clean, istiqomah, disciplined and patient in learning. The aim of this research is 1. To know the steps for Islamic character education in learning Tahfidz Al-Qur'an. 2. To find out the implementation of Islamic character education in learning Tahfidz Al Qur'an.